A Systematic Review of Determinants Influencing Family Planning and Contraceptive Use - Pipit Feriani; Esti Yunitasari; Ferry Efendi; Ilya Krisnana; Rini Ernawati; Niken A. Tianingrum; Nurus Safaah (Wolters Kluwer Medknow Publications, 2024)
Background: Reproductive health, crucial for public health and sustainable development, encompasses family planning and contraceptive use. However, global disparities persist in the adoption of family planning, highlighting the need for a comprehensive understanding of the complex factors shaping these reproductive health choices. Materials and Methods: Following Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines, we conducted a systematic search of the Scopus, ScienceDirect, PubMed, Web of Science, and ProQuest databases from July to August 2023. Inclusive criteria covered various study designs and populations, ranging from individuals to communities, and encompassed sociocultural factors. The review included open access articles published between 2018 and 2023, utilizing a combination of the keywords: Family planning determinants, Contraceptive use factors, Sociocultural factors in family planning, Individual-level influences on family planning, and Factors affecting contraceptive choices. Results: Data from 25 selected studies underscore the critical influence of determinants at both individual and community levels in shaping family planning behaviors. Key drivers at the individual level included education, age, knowledge, and attitudes. At the community level, factors such as geographical disparities and healthcare accessibility played pivotal roles. Sociocultural determinants, including media exposure, gender norms, and spousal dynamics, highlighted the need for culturally sensitive strategies. Conclusions: Advancing equitable family planning requires education, improved access, peer influence, and the active participation of husbands and male partners. Comprehensive programs should bridge the gap between knowledge and action, reduce disparities, and ensure equal access to contraception. Context-specific research and evaluating interventions are crucial steps toward achieving global reproductive health objectives.